2018
DOI: 10.5603/fhc.a2018.0014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of genistein on insulin pathway-related genes in mouse differentiated myoblast C2C12 cell line: evidence for two independent modes of action

Abstract: The results of this study showed that depending on the concentration and time of incubation genistein significantly affects glucose and lipid metabolism and at low concentration modifies expression pattern of a few genes in C2C12 cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Glucose-related pathways, such as tyrosine phosphorylation, changes in insulinreceptor counts, disrupted glucose transportation, and intracellular phosphorylation [28]. Besides, the alphaglucosidase enzyme can be inhibited by the genistein [29]. Hyperglycemia can decrease by inhibiting the alpha-glucosidase enzyme's effect when the amount of monosaccharides that can be consumed by the gut is reduced [30].…”
Section: Genistein As Antioxidantmentioning
confidence: 99%
“…Glucose-related pathways, such as tyrosine phosphorylation, changes in insulinreceptor counts, disrupted glucose transportation, and intracellular phosphorylation [28]. Besides, the alphaglucosidase enzyme can be inhibited by the genistein [29]. Hyperglycemia can decrease by inhibiting the alpha-glucosidase enzyme's effect when the amount of monosaccharides that can be consumed by the gut is reduced [30].…”
Section: Genistein As Antioxidantmentioning
confidence: 99%
“…Using a mouse culture model C 2 C1 2 myogenic cell line [227], glucose transport and oxidation of fatty acids by measuring the radioactivity of 2-deoxy-D-[1,2-3 H]-glucose and [9,10-3 H]palmitic acid, respectively, were investigated. The dose of genistein was 0.1, 1, and 50 μM.…”
Section: Antidiabetes and Effects On Lipidmentioning
confidence: 99%
“…In this regard, it has been hypothesized that activation of the PI3K/AKT signaling pathway by SARS‐CoV‐2 contributes to inducing glucose uptake through GLUT‐4 leading to increase glycolysis and viral replication in host cells (Malgotra & Sharma, 2021 ). Since it has been reported that genistein is a potent and direct inhibitor of GLUT‐4 (Lewicki et al, 2018 ), the direct inhibition of GLUT‐4 by genistein from one side and inhibition of the PI3K/AKT pathway from another side could disrupt the viral replication (Figure 2 ). Furthermore, due to the involvement of the PI3K/AKT pathway in clot formation, targeting this pathway by genistein could prevent thrombosis in COVID‐19 patients.…”
Section: Pharmacological Effects Of Genistein As a Probable Beneficia...mentioning
confidence: 99%